User experience with pregnancy tracker mobile apps: Findings from comment-based qualitative study - Md. Alamgir Hossain; Janet Perkins; Md Tanvir Hasan; Sharon Low Bee Lian; Ribica Chowdhury; Md. Tanzirul Alam; Anisuddin Ahmed; Mohammad Sohel Shomik; Shams El Arifeen; Ahmed Ehsanur Rahman; Aniqa Tasnim Hossain; M. Shafiqur Rahman (PLoS ONE, 2025)
Background Worldwide, millions of pregnant women use pregnancy-related apps to monitor their baby’s growth and development. While most of the apps are user-friendly, not all of them are equally appealing. This study aimed to explore the user experience (UX) of pregnancy tracker mobile apps used by pregnant women. Methods This study explored the dynamics between users’ experiences and multifaceted dimensions of advanced features, high-quality materials and information, strict privacy policies, problem-solving abilities, and the usefulness of app features and contents. This study applied reviewers’ comment-based qualitative study, accessing crowdsourced data gathered from different pregnancy tracker app websites. A thematic and content analysis approach was used. Results This study found that when users are satisfied with using advanced content and features, it aligns with their perceived self-righteousness and rationality, and reflects their cultural values and expectations of using the apps. Conversely, when users encounter challenges such as erroneous baby size comparison and app updating issues, they perceive these as disadvantages of the apps utilised. Moreover, the study sheds light on the specific desires of pregnant women, highlighting their expectations for content that addresses their physical and mental well-being, as well as their unborn babies. The desire for free access reflects the cultural emphasis on cost-effectiveness, while the willingness to invest financially in enhanced experiences demonstrates the recognition of the value and potential benefits of improved content and features. This study also provides valuable insights into the complex relationship between users’ experiences, cultural values, advanced features, high-quality materials and information, privacy policies, problem-solving abilities, and relevant content in creating positive app experiences that align with users’ cultural expectations and needs. Conclusion This study provides essential insights into the user experience and underscores the importance of a user-centric design approach for developers. By capturing the current landscape of these digital tools, can provide valuable feedback for the enhancement of existing applications and guide the development of future iterations, ensuring the diverse preferences and expectations of pregnant women worldwide.